Ruska revolucija in slovensko narodno vprašanje - Malmenvall, Simon (Bogoslovni vestnik, 2023)
Franc Grivec (1878–1963), a long-time professor at the Faculty of Theology in Ljubljana, is considered a pioneer in systematic research of Eastern Christianity among Slovenian authors. A significant part of Grivec’s published work is dedicated to the ideational analysis of the October Revolution of 1917, which presented a topical public issue of his time, conditioned by socio-economic change and the seeking of new collective identities. This is most thoroughly addressed in the monograph for a wider audience (National Consciousness and Bolshevism) originally written by Grivec based on his lectures to the primaryand high-school teachers of Ljubljana in 1944. According to Grivec, the extremism of the Bolsheviks represents a part of the wider mechanism of Russian cultural history, in which the concept of a messianic mission, starting with the idea of Moscow as the “Third Rome,” appeared several times. The mentioned author calls on Catholic intellectuals to assert Christian principles in public and foster a reflected national consciousness as opposed to the internationalist socialism, in order to prevent the success of the revolution on Slovenian soil. His views are organically complemented by France Dolinar (1915–1983), a representative of the younger generation of Catholic scholars of the time, who decided to live in emigration due to the political pressures in his homeland. Dolinar draws close to Grivec with the emphasis on the engagement for the common national cause against the “political partisan mindset”; on the other hand, Dolinar surpasses Grivec with his idea for the independent Slovenian state, which would be a real opposite to the socialist theory on the extinction of nations.
Keywords: boljševizem; Bolshevism; Catholic social teaching; Dolinar, France; Eastern Orthodoxy; Grivec, Franc; history of higher education; katoliški družbeni nauk; pravoslavje; ruska kultura; Russian culture; Slovenian national question; slovensko narodno vprašanje; zgodovina visokega šolstva